Cocaine addicted to cytoskeletal change and a fibrosis high. Issue 2 (22nd January 2019) - Verma, Avnish; Bennett, Jason; Örme, Ayşe Merve; Polycarpou, Elena; Rooney, Brian
Abstract: Cocaine is one of the most widely abused illicit drugs due to its euphoric and addictive properties. Cocaine‐mediated cognitive impairments are the result of dynamic cytoskeletal rearrangements involved in mediating structural and behavioural plasticity. Cytoskeletal changes initiated following cocaine abuse are regulated by the Rho family of GTPases with significant downstream activity in key actin binding proteins. Moreover, signalling via the endoplasmic reticulum chaperone protein, sigma‐1 receptor has highlighted the possibility of cocaine regulated pathology in other organ systems. However, the question of whether upstream stimulation of such a high affinity binding receptor is directly involved in cocaine‐mediated cytoskeletal changes at present remains unknown. In this review, we describe the functional role of key cytoskeletal regulators in response to cocaine‐induced signalling cues. In addition, we ascertain the extent of whether global cytoskeletal modulators involved in cocaine‐induced neurological stimulation can be used as a platform for future studies into elucidating its fibrotic potential within the hepatic microenvironment. A focus on aspects still poorly understood relating to the nonneuronal pathological impact of cocaine is discussed in the sphere of hepatic dysregulation. Lastly, we suggest that cocaine may mediate its pathological capacity via the sigma1 receptor in regulating hepatoxicity, hepatic stellate cells activity, cytoskeletal dynamics, and the transcriptional regulation of key hepato‐fibrogenic modulators.